Age-stratified anti-Müllerian hormone (AMH) nomogram: a comprehensive cohort study including 22.920 women - Aslan, Kiper; Kasapoglu, Isil; Kosan, Bahadir; Tunali, Aylin; Tellioglu, Ilayda; Uncu, Gurkan (Frontiers in Endocrinology, 2025)
BackgroundInfertility rates have been rising globally, necessitating accurate assessment tools for ovarian reserve. Anti-Müllerian hormone (AMH) is a key biomarker for evaluating ovarian reserve, yet age-stratified reference data remain limited. Establishing an AMH nomogram could enhance fertility counseling and treatment planning.ObjectiveTo develop an age-stratified AMH nomogram to improve the understanding of ovarian reserve across reproductive ages and assist in comparing individual AMH values with age-specific thresholds, aiding in the baseline infertility work-upMethodsThis retrospective cohort study analyzed AMH test results from a tertiary university hospital’s electronic database between April 2015 and June 2024. Data were collected from various departments, excluding women younger than 18 or older than 45 years. Median AMH levels and interquartile ranges were calculated for each age group. The prevalence of diminished ovarian reserve (DOR), defined as AMH <1.2 ng/mL, was determined. Statistical analyses, including correlation testing and subgroup comparisons across different clinical settings, were performed using SPSS version 22 (IBM Corp., Armonk, NY, USA).ResultsA total of 22,920 AMH results were analyzed after excluding patients outside the 18–45 age range and those with incomplete data. More than half of the AMH tests were from women aged 24–33 years. The results demonstrated a significant negative correlation between age and AMH levels, with a median AMH value dropping below 1.2 ng/mL by age 36. The prevalence of DOR increased from 15.9% at age 18 to 96% at age 45. Additionally, women from the Endometriosis Unit had significantly lower AMH levels (median 1.6 ng/mL) compared to other departments (median 2.03 ng/mL). The age-stratified AMH distribution remained consistent even when patients from ART (Assisted Reproductive Technology) centers, REI (Reproductive Endocrinology and Infertility), and the Endometriosis Unit were excluded.ConclusionThis study provides an age-stratified AMH nomogram that can serve as a valuable tool for clinicians to assess ovarian reserve more accurately. The sharp decline in AMH levels, particularly after age 36, emphasizes the need for timely fertility evaluations and interventions, particularly in populations at risk for diminished ovarian reserve, such as those with endometriosis.